The influence of human capital and corporate governance characteristics towards firm’s performance in Malaysian listed companies / Noorain Omar and Roshima Said - Omar, Noorain; Said, Roshima (Research Management Institute, 2012)
Financial crisis that attacked Malaysia and other Asian countries in the year 1997 brought a lot of lessons to learn. Malaysian government in ensuring the survival of its economy during the crisis took many actions, including the implementation of capital controls. In Malaysia, attempts to contain further devaluation caused a higher level of interest rate and credit contraction. This caused severe contractions in output and corporate profitability which was reflected in massive fall of equity prices. The crisis also attacked the Malaysian stock prices, where the Kuala Lumpur Composite Index decline by 72% during the period from end-June 1997 to end-August 1998. In Malaysia, many companies have experienced bankruptcy, being de-listed from the Bursa Malaysia and are experiencing financial distress. This phenomenon has created a new area for research. As there are less research and reports on the relationship between human capitals explicitly, corporate governance characteristics and the firm performance in Malaysia, the researchers have taken steps to investigate more about this matter especially in the context of Malaysia. The research methodology that shall be used is the analysis of annual reports of Malaysian listed companies on Bursa Malaysia for the year ended 2009. This study is expected to reveal that human capital and corporate governance characteristics do influence the firm performance.